Heterologous expression of Septoria lycopersici tomatinase in Cladosporium fulvum: Effects on compatible and incompatible interactions with tomato seedlings - Melton, R.; Flegg, L.; Brown, J.; Oliver, Richard; Daniels, M.; Osbourn, A. (1998)
The anti-fungal, steroidal, glycoalkaloid saponin, α-tomatine, is present in uninfected tomato plants in substantial concentrations, and may contribute to the protection of tomato plants against attack by phytopathogenic fungi. In general, successful fungal pathogens of tomato are more resistant to α-tomatine in vitro than fungi that do not infect this plant. For a number of tomato pathogens, this resistance has been associated with the ability to detoxify α-tomatine through the action of enzymes known as tomatinases. In contrast, the biotrophic tomato pathogen Cladosporium fulvum is sensitive to α-tomatine and is unable to detoxify this saponin. This paper describes the effects of heterologous expression of the cDNA encoding tomatinase from the necrotroph Septoria lycopersici in two different physiological races of C. fulvum. Tomatinase-producing C. fulvum transformants showed increased sporulation on cotyledons of susceptible tomato lines. They also caused more extensive infection of seedlings of resistant tomato lines. Thus, α-tomatine may contribute to the ability of tomato to restrict the growth of C. fulvum in both compatible and incompatible interactions.